Breeding experience and foraging behaviour of Imperial Shags (Leucocarbo atriceps) in Argentina - Harris, Sabrina (2014)
Breeding success depends on efficient foraging behaviour by breeding individuals. However, foraging skills are acquired over time and foraging behaviour is expected to be optimised over the course of successive breeding events. In 2008, 32 Imperial Shags (Leucocarbo atriceps) breeding at the Punta León colony, Argentina, either with prior breeding experience (4 males and 9 females) or without (10 males, 9 females), were fitted with tracking devices to record one foraging trip during the early chick-rearing period. Birds did not differ in the maximum distance from the colony or duration of foraging trips, but males spent more time flying than females. Inexperienced individuals spent more time diving than experienced individuals, and inexperienced males in particular spent more time flying and performed more dives than other birds. Experienced males and females differed in the areas that they searched most intensively, and inexperienced males used different areas from experienced males. This study shows the importance of considering sex- and age-related differences when studying behavioural aspects, such as foraging patterns in seabirds.